A Research Report on “Artificial Intelligence Drive Predictive Analytics in Decision Making E-Commerce” - Aryan Shingala; Jignesh Vidani (MultiTech Publisher, 2024)
This research explores how Artificial Intelligence (AI) is revolutionizing decision-making in e-commerce through predictive analytics. Predictive analytics leverages AI-powered algorithms to analyze vast amounts of customer data, including browsing behavior, purchase history, and preferences, to anticipate future trends and behaviors. This capability enables e-commerce businesses to personalize customer experiences, optimize pricing strategies, forecast demand, and improve inventory management. The study highlights the role of AI techniques such as machine learning, deep learning, and natural language processing in identifying patterns and generating actionable insights. By focusing on case studies and real-world applications, this research demonstrates how AI-driven predictive analytics enhances operational efficiency, boosts customer satisfaction, and drives business growth in the competitive e-commerce landscape